Impact of Flash Floods On Agri-based Livelihoods In Sylhet Haor Basin - Akter, N; Islam, MR; Karim, MA; Miah, MG; Rahman, MM (Annals of Bangladesh Agriculture, 2022)
Bangladesh is most vulnerable to natural disasters and climate change. Over the past few decades, flash floods have frequently affected the livelihood of people in the Sylhet Haor Basin. This study highlights the causes of increased flash floods, their impact on farming practices and livelihoods, and possible solutions to flash flood risk in the Sylhet Haor Basin. Data were collected using a pre-tested structured questionnaire from randomly selected 298 Haor farmers in high and moderately vulnerable flash flood zones across the Haor region during November 2021 and April 2022. In moderately vulnerable areas, the lack of rivers and canal dredging was the main factor contributing to flash flood deterioration. Index scores and ranks revealed that flash floods most severely affect the primary production sector (agriculture) and threaten the lives and livelihoods of the local populace in high- and moderately flood-prone areas. After the severe flash flood, farmers were forced to turn to other occupations instead of agriculture for their livelihood. To reduce the impact of flash floods on particular features or entire wetlands, most farmers preferred the construction of embankments over sandbags, concrete or stone dams, submergible embankments, and rubber dams. For flash flood risk management, farmers in high- and moderately flash flood-vulnerable areas emphasize the construction of higher dams and embankments and the installation of more flood barriers (dams/embankments). The concerned flash flood management agencies could incorporate the key findings of this study while formulating risk mitigation strategies for the Sylhet Haor Basin. Ann. Bangladesh Agric. (2022) 26 (1) : 61-73